2015
DOI: 10.1038/nature14307
|View full text |Cite
|
Sign up to set email alerts
|

An enigmatic plant-eating theropod from the Late Jurassic period of Chile

Abstract: Theropod dinosaurs were the dominant predators in most Mesozoic era terrestrial ecosystems. Early theropod evolution is currently interpreted as the diversification of various carnivorous and cursorial taxa, whereas the acquisition of herbivorism, together with the secondary loss of cursorial adaptations, occurred much later among advanced coelurosaurian theropods. A new, bizarre herbivorous basal tetanuran from the Upper Jurassic of Chile challenges this conception. The new dinosaur was discovered at Aysén, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 20 publications
0
61
3
Order By: Relevance
“…; Novas et al . ). In fact, 1 kg is large for extant bird species, which have a modal body mass around 100 g (Brown ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Novas et al . ). In fact, 1 kg is large for extant bird species, which have a modal body mass around 100 g (Brown ).…”
Section: Discussionmentioning
confidence: 97%
“…), the ceratopsian Graciliceratops (Maryanska & Osmólska ), mononychine theropods (which have small body sizes but occur after the Aptian and so could not be analysed in our study) and also the early possible tetanuran Chilesaurus (~1 kg; immature individual; Novas et al . ) (Table ). Chilesaurus was not included in our analyses because adult mass estimates are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Barrett, 2014, and references therein), except for a tentative coupling between the decline of cycadophytes and stegosaurs during the earliest Cretaceous (Butler et al, 2009a,b). The only known herbivorous tetanuran theropod lineage in the Jurassic has no known Cretaceous representative (Novas et al, 2015). It has been suggested that medium-sized theropods underwent a substantial decline across the J/K boundary, and were replaced by larger-bodied carcharodontosaurids and spinosaurids (Novas et al, 2013;Tortosa et al, 2014).…”
Section: (3) Biotic Interactions and Evidence For A Faunal Turnover (mentioning
confidence: 99%
“…They were predominantly carnivorous, but some derived lineages evolved omnivorous and herbivorous diets (Barrett , ; Zanno & Makovicky ; Novas et al . ; Lautenschlager ). Non‐avian theropod fossils have been found on all continents and in all environments, occupying an array of ecological niches (Henderson ; Amiot et al .…”
mentioning
confidence: 99%